2015
DOI: 10.1159/000369917
|View full text |Cite
|
Sign up to set email alerts
|

Rebound Thrombocytosis following Induction Chemotherapy Is an Independent Predictor of a Good Prognosis in Acute Myeloid Leukemia Patients Attaining First Complete Remission

Abstract: There are very few data about the relationship between acute myeloid leukemia (AML) prognosis and bone marrow recovery kinetics following chemotherapy. In this study, we aimed to assess the prognostic importance and clinical associations of neutrophil and platelet recovery rates and rebound thrombocytosis (RT) or neutrophilia (RN) in the postchemotherapy period for newly diagnosed AML patients. De novo AML patients diagnosed between October 2002 and December 2013 were evaluated retrospectively. One hundred pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…27 Also, rebound thrombocytosis following induction chemotherapy is an independent predictor of a good prognosis in AML patients attaining first CR. 28 In our study, those who achieved CR after induction therapy, those who did not have fibrosis in their bone marrow biopsy, those who had Auer body in their bone marrow aspirates, and those who were classified as having favorable cytogenetic risk had statistically significantly longer overall survival time, but ECOG performance score was not found to be a prognostic factor. In addition, in our AML patients rebound thrombocytosis following induction chemotherapy was not found to be a prognostic factor either.…”
mentioning
confidence: 53%
“…27 Also, rebound thrombocytosis following induction chemotherapy is an independent predictor of a good prognosis in AML patients attaining first CR. 28 In our study, those who achieved CR after induction therapy, those who did not have fibrosis in their bone marrow biopsy, those who had Auer body in their bone marrow aspirates, and those who were classified as having favorable cytogenetic risk had statistically significantly longer overall survival time, but ECOG performance score was not found to be a prognostic factor. In addition, in our AML patients rebound thrombocytosis following induction chemotherapy was not found to be a prognostic factor either.…”
mentioning
confidence: 53%
“…He had two factors that may explain the uncontrollable increase in platelet count. First, it has been reported that up to 40% of patients suffer thrombocytosis after chemotherapy aplasia for AML . In addition, the presence of CALR mutation represents a strong stimulus for thrombopoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several studies have shown a negative correlation between platelet count and OS before treatment, which can be used as an independent predictor of AML prognosis [25][26][27][28][29][30] . Other factors related to initial platelets, including rebound thrombocytosis, platelet production, and platelet recovery time after platelet induction chemotherapy, are independent prognostic predictors of AML or acute lymphocytic leukemia (ALL) Index [31][32][33] .…”
Section: Discussionmentioning
confidence: 99%